THE INFLUENCE OF THE SCHOOL PRINCIPAL'S PARTICIPATIVE LEADERSHIP STYLE, INFRASTRUCTURE AND EMOTIONAL INTELLIGENCE ON PRIMARY TEACHER PERFORMANCE - PARDEDE, Marulas; ISTARYATININGTIAS, Istaryatiningtias; GHANI, Abd Rahman A. (Journal of Education and Leadership in Education, 2023)
This research was conducted with the aim of determining the impact of the principal's participative leadership style, infrastructure and emotional intelligence on the performance of elementary school teachers in Kembangan District, West Jakarta. This research is quantitative because the data analyzed is in the form of numbers obtained from respondents' answers which were distributed to 85 elementary school teachers. The research is contextual operational in nature by using hypothesis testing to make temporary guesses regarding the influence of the independent variable on the dependent variable. Data collection was carried out using a Google Form questionnaire with a horizontal time is cross sectional. The results of research conducted with the help of Smartpls statistical software are that the principal's participative leadership style has no effect on teacher performance, while infrastructure and emotional intelligence have an influence on teacher performance